Philosophy in the Islamic World : Volume 4/1: 19th-20th Centuries: The Arabic-Speaking Region - Adamson, Peter; Kügelgen, Anke; Rudolph, Ulrich (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2025)
Philosophy in the Islamic World is a comprehensive and unprecedented four-volume reference work devoted to the history of philosophy in the realms of Islam, from its beginnings in the eighth century AD down to modern times. The focus of this fourth installment of the series, divided into two volumes, is the 19th and 20th centuries and geographically on the Arab countries, the Ottoman-Turkish region, Iran, and Muslim South Asia. During this time philosophy was pursued at Islamic institutions and increasingly in Western-style universities, but philosophy also had an impact beyond academia. In each chapter, an international expert on philosophy in this period explores the teachings of individual philosophers, philosophical movements (philosophy of religion, logical empiricism, deconstructionism, etc.), and schools (for instance the continuation of Mullā Ṣadrā's philosophy of being). Debates over cultural authenticity, political rule, gender, and other major issues are also presented. This is the English version of the relevant volume of the Ueberweg, the most authoritative German reference work on the history of philosophy, which updates the German version ( Philosophie in der Islamischen Welt Band 4/1: 19. und 20. Jahrhundert. Arabischer Sprachraum , Basel: Schwabe, 2021) by providing references to the latest scholarly literature. Contributors Katajun Amirpur, Sadik Jalal al-Azm, Serpil Çakır, Frank Darwiche, Bettina Dennerlein, Sarhan Dhouib, Zeynep Direk, Michael Frey, Urs Gösken, Ursula Günther, Reza Hajatpour, Jan-Peter Hartung, Christoph Herzog, Elisabeth Susanne Kassab, Mohamed Aziz Lahbabi, Kata Moser, Sait Özervarlı, Nils Riecken, Sajjad Rizvi, Ruggero Vimercati Sanseverino, Roman Seidel and Harald Viersen. See Less